The cost of non-Europe in the sharing economy: economic, social and legal challenges and opportunities - Goudin, Pierre (Brussels, 2016)
"This 'Cost of Non-Europe' study examines the current economic, social and legal state of play regarding the sharing economy in the European Union, and identifies the cost of the lack of further European action in this field. The assessment of existing EU and national legislation confirms that there are still significant implementation gaps and areas of poor economic performance. The subsequent examination of areas where it was believed that an economic potential exists highlighted that substantial barriers remain, hindering the achievement of the goals set out in the existing legislation. Moreover, some issues are not or are insufficiently addressed (e.g. status of workers employed by sharing economy service providers). Consequently, more European action would be necessary to achieve the full economic potential of the sharing economy. In doing so, policy-makers should seek to ensure an adequate balance between creative freedom for business and the necessary regulatory protection. This research estimates the potential economic gain linked with a better use of capacities (otherwise under-used) as a result of the sharing economy is €572 billion in annual consumption across the EU-28. This figure should nevertheless be considered with caution; substantial barriers prevent the full benefits from being realised, and could reduce the value of potential increased use to up to €18 billion in the shorter-term and up to €134 billion in the medium and longer term, depending on the scale of regulatory obstacles."